Developments in Management Science in Engineering 2017 Perspectives from Scientific Journal Reports - Xu, Jiuping (Cambridge Scholars Publisher, 2019)
Management science in engineering (MSE) is playing an increasingly important role in modern society. In particular, the development of efficient and innovative managerial tools has significantly influenced the research progress of management science. As research is vital for the propagation of leading-edge methods, journal evaluation and classification are critical for scientists, researchers, engineers, practitioners, and graduate students. This book identifies the main research categories of MSE, and evaluates and classifies each MSE journal. It represents the outcome of joint efforts from scientific board members, research fellows, and members of various professional societies. It is ideal for scientists, researchers, practitioners, engineers, graduate students and upper-level undergraduates in engineering management, civil engineering, industrial engineering, environmental engineering, energy engineering, information engineering, and agricultural engineering